The “Survival Pending Revolution” COVID-19 vaccination campaign: an example of critical communication theory in action - Schillinger, Dean; Cortez, Gabriel; Lee, Michelle (Frontiers in Public Health, 2023)
We carried out a two-phase, qualitative evaluation of a novel public health campaign to promote COVID-19 vaccination among youth and young adults of color (YOC), called Survival Pending Revolution. The campaign, commissioned by California’s Department of Public Health, was created by YOC spoken word artists, under the direction of the organization, Youth Speaks. In phase 1, we describe the attributes of the campaign’s 9 video-poems and coded the predominant themes conveyed. In phase 2, we carried out a comparative health communication study to assess the content’s potential value. We exposed a sample of the target audience (YOC) to content from Survival Pending Revolution and a widely viewed campaign (The Conversation). Using a focus group, we solicited participants’ views using a semi-structured approach. We summarized the themes that arose when participants reflected on the attributes of each campaign. Findings from phase 1 reveal how engaging YOC artists who embrace Youth Speaks’ philosophy of harnessing “life as primary text” resulted in content that is aligned with critical communication theory, focusing on structural determinants of health, including themes of overcoming oppressive systems, health and social inequities, and medical discrimination and mistrust. Findings from phase 2 reveal that this arts-based campaign based on such critical communication theory, when compared to a more traditional campaign, promotes message salience, fosters emotional engagement, and provides a form of validation among historically oppressed groups such that they may be more open to, and potentially act on, the COVID vaccination communications to which they are exposed. As an example of critical communication, Survival Pending Revolution campaign encourages health-promoting behavioral decisions while calling out the structural determinants of health that shape risks of exposures and constrain free choice. Engaging uniquely gifted members of marginalized populations as creators and messengers of campaigns leads to content that is aligned with a critical communication approach, whose goal is to aid disparity populations in both resisting and navigating systems that continue to locate them on the margins of society. Our evaluation of this campaign suggests it represents a promising formative and interventional approach to engendering trust in public health messaging and promoting health equity.